The regulatory repertoire of PLZF and SALL4 in undifferentiated spermatogonia - Lovelace, Dawn L. (Development, 2016)
Spermatogonial stem cells (SSCs) maintain spermatogenesis throughout adulthood through balanced self-renewal and differentiation, yet the regulatory logic of these fate decisions is poorly understood. The transcription factors Sal-like 4 (SALL4) and promyelocytic leukemia zinc finger (PLZF; also known as ZBTB16) are known to be required for normal SSC function, but their targets are largely unknown. ChIP-seq in mouse THY1(+) spermatogonia identified 4176 PLZF-bound and 2696 SALL4-bound genes, including 1149 and 515 that were unique to each factor, respectively, and 1295 that were bound by both factors. PLZF and SALL4 preferentially bound gene promoters and introns, respectively. Motif analyses identified putative PLZF and SALL4 binding sequences, but rarely both at shared sites, indicating significant non-autonomous binding in any given cell. Indeed, the majority of PLZF/SALL4 shared sites contained only PLZF motifs. SALL4 also bound gene introns at sites containing motifs for the differentiation factor DMRT1. Moreover, mRNA levels for both unique and shared target genes involved in both SSC self-renewal and differentiation were suppressed following SALL4 or PLZF knockdown. Together, these data reveal the full profile of PLZF and SALL4 regulatory targets in undifferentiated spermatogonia, including SSCs, which will help elucidate mechanisms controlling the earliest cell fate decisions in spermatogenesis.